Analysis Juridical Public Participation Formation of Regional Regulation No. 3 of 2017 on The Implementation of The Business Entertainment In Wonosobo Regency - Amin Syarifudin; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
To set the order and comfort in the Wonosobo regency and Goverment Wonosobo regency make Region Regulation No. 3 of 2017 on the Implementation of Enterprise Entertainment in Wonosobo. This is associated with the rise of karaoke business premises in Wonosobo. But after the regulation passes reap a lot of conflict in the community. This makes the writer interested in making. Juridical Analysis of Public Participation in Formation of Regional Regulation Number. 3 of 2017 on the Implementation of Enterprise Entertainment in Wonosobo,Method of approach used in this study is a sociological juridical methods, using the principles and legal principles in reviewing, view, and analyze problems.According to Act No. 12 of 2011 Establishment Regulation Legislation. Article 96